2022
DOI: 10.3390/cells11244048
|View full text |Cite
|
Sign up to set email alerts
|

Cfap91-Dependent Stability of the RS2 and RS3 Base Proteins and Adjacent Inner Dynein Arms in Tetrahymena Cilia

Abstract: Motile cilia and eukaryotic flagella are specific cell protrusions that are conserved from protists to humans. They are supported by a skeleton composed of uniquely organized microtubules—nine peripheral doublets and two central singlets (9 × 2 + 2). Microtubules also serve as docking sites for periodically distributed multiprotein ciliary complexes. Radial spokes, the T-shaped ciliary complexes, repeat along the outer doublets as triplets and transduce the regulatory signals from the cilium center to the oute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 57 publications
3
39
0
Order By: Relevance
“…A recent EM study showed that this elongated protein forms the base of the RS2 radial spoke, extends parallel to the CCDC39/40 ruler and through the N-DRC, and contacts RS3 70,82 . Moreover, defective CFAP91 function in both humans and Tetrahymena is associated with disruption specifically of the RS3 radial spoke 79,81 . Little else is known of CFAP91 function, so it is significant that multiple XLs in our dataset also linked CFAP91 directly to CCDC96 (Figure 6B , dark blue ), which connects RS3 to the NDR-C 83 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent EM study showed that this elongated protein forms the base of the RS2 radial spoke, extends parallel to the CCDC39/40 ruler and through the N-DRC, and contacts RS3 70,82 . Moreover, defective CFAP91 function in both humans and Tetrahymena is associated with disruption specifically of the RS3 radial spoke 79,81 . Little else is known of CFAP91 function, so it is significant that multiple XLs in our dataset also linked CFAP91 directly to CCDC96 (Figure 6B , dark blue ), which connects RS3 to the NDR-C 83 .…”
Section: Resultsmentioning
confidence: 99%
“…These interactions in Tetrahymena prompted us to explore the effect of CFAP91 loss in vertebrate multiciliated cells. First, we showed that knockdown (KD) of CFAP91 in Xenopus multiciliated cells recapitulated the known effect of genetic loss in humans and Tetrahymena 79,81 . For example, we observed specific loss of the RS3 subunit CFAP251 (Figure 6G), while the RS1/RS2 subunit Rsph1 was unaffected (Figure 6H).…”
Section: A Dense Network Of Ciliopathy Proteins Associated With the C...mentioning
confidence: 92%
See 1 more Smart Citation
“…Recent advances in artificial intelligence, biochemical techniques, and cryo-electron microscopy (cryo-EM) facilitated the analysis of the axonemal structures, and numerous components were detected among RS, N-DRC and DMTs, which may serve as hubs to stabilize the axoneme (Bazan et al, 2021; Leung et al, 2023; Walton et al, 2023; Zhou et al, 2023). Such as, CFAP91 is identified to extend from the base of RS2 through the N-DRC base plate to the RS3, and stabilizes RS2 and RS3 on the DMTs (Bicka et al, 2022; Dymek et al, 2011; Gui et al, 2021). CFAP57 also extends through the N-DRC and interacts with RS3 via its C-terminal region (Ghanaeian et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Modern proteomics methods have also recently become useful in neurodegenerative diseases in developing methods for the analysis [ 8 ] and identification of new biomarkers for early diagnosis and disease progression [ 9 , 10 , 11 , 12 ]. Many proteomics studies are also being conducted to identify novel proteins and biological functions in plants [ 13 , 14 ] and on model organisms such as Tetrahymena thermophila to elucidate the involvement of many key proteins in the basis of biological processes [ 15 ]. There are several reports in the literature on the use of proteomic methods in antidoping tests [ 16 ], early medical diagnosis [ 17 , 18 , 19 , 20 ], and candidates for vaccine production [ 21 ].…”
Section: Introductionmentioning
confidence: 99%